2020
DOI: 10.3390/ijerph17155338
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Job Insecurity and Depressive Symptoms among Italian Dentists: The Moderating Role of Fear of COVID-19

Abstract: Containment measures adopted to reduce the spread of coronavirus disease 2019 (COVID-19) have produced a general perception of job insecurity. Dentists have been highly affected by such measures, as they represent an easy source of contagion. As perceived job insecurity is associated with psychological distress and Italian dentists have been highly affected by the COVID-19 outbreak in terms of potential financial loss and the risk of being infected, this study aimed at assessing whether the fear of COVID-19 mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
136
1
8

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 137 publications
(159 citation statements)
references
References 48 publications
14
136
1
8
Order By: Relevance
“…This finding is similar to the results of cross-sectional surveys among dentists from China, India, Israel, Italy, and the U.K. [ 19 ], as well as U.K. frontline HCWs, where no gender differences were revealed [ 3 ]. By contrast, several other studies have revealed that female dentists showed significantly higher levels of self-reported anxiety [ 13 ], depression [ 12 ], and stress [ 21 ], confirming that women are at higher risk of depressive symptoms than men [ 47 ]. Therefore, our findings should be treated with caution, because the majority of participants identified as women (78.9%) and it may be that there was insufficient power to detect differences.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…This finding is similar to the results of cross-sectional surveys among dentists from China, India, Israel, Italy, and the U.K. [ 19 ], as well as U.K. frontline HCWs, where no gender differences were revealed [ 3 ]. By contrast, several other studies have revealed that female dentists showed significantly higher levels of self-reported anxiety [ 13 ], depression [ 12 ], and stress [ 21 ], confirming that women are at higher risk of depressive symptoms than men [ 47 ]. Therefore, our findings should be treated with caution, because the majority of participants identified as women (78.9%) and it may be that there was insufficient power to detect differences.…”
Section: Discussionmentioning
confidence: 98%
“…This is because dental healthcare delivery requires close physical contact between patients and specialists, while dental procedures generate aerosols, which pose potential risks to operators and patients [ 11 ]. Moreover, for these reasons, severe restrictions in dental practice have been adopted by governments to avoid this source of contagion [ 12 , 13 ]. In several countries, dentists have been allowed to practice only emergency/urgent procedures during the whole period of the lockdowns [ 12 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this pandemic scenario, fear of COVID-19 contagion seems to be an exacerbator of distress and has been found to be associated with negative mental health outcomes [ 4 , 12 , 13 ]. In this line, Wankowicz et al [ 14 ] reported that healthcare workers who are exposed to SARS-CoV-2-infected patients in emergency wards, infectious wards, and intensive care units are at a much higher risk of experiencing symptoms of anxiety and depression than HCW working in other wards.…”
Section: Introductionmentioning
confidence: 99%